Innovativeness of the Czech Republic and the Slovak Republic - Weiszer, Lukáš (2025)
This thesis aims to analyze the innovativeness of the Czech Republic and the Slovak Republic based on four selected attributes: 1. Quality of Education 2. Political and Business Foundations 3. Knowledge and R&D 4. Digital Infrastructure and Readiness It is especially interesting to examine the attributes of innovation of these two countries as they share long history of being one state, however, the Czech Republic constantly performs better in innovation indices such as GII or SII. The firt chapter provides definitions of innovation and innovativeness, and the link between innovativeness and economic growth. Subsequently, brief overview of the two economies is provided, followed by deeper examination of the performance of countries within the innovation indices. Second chapter provides a deeper insight into the selected attributes and analyzes the possible causes of better performance in the Czech Republic, in order to provide recommendations for the Slovak Republic to improve its performance.